PCSK9 promotes arterial medial calcification. (April 2022) - Lupo, Maria Giovanna; Bressan, Alessandro; Donato, Maristella; Canzano, Paola; Camera, Marina; Poggio, Paolo; Greco, Maria Francesca; Garofalo, Mariangela; De Martin, Sara; Panighel, Giovanni; Ruscica, Massimiliano; Baragetti, Andrea; et al.
Abstract: Background and aims: A complex interplay among chronic kidney disease (CKD), lipid metabolism and aortic calcification has been recognized. Here we investigated the influence of kidney function on PCSK9 levels and its potential direct action on smooth muscle cells (SMCs) calcification. Methods and Results: In a cohort of 594 subjects, a negative association between glomerular filtration rate and plasma PCSK9 was found. Atherosclerotic cardiovascular disease, as co-morbidity, further increased PCSK9 plasma levels. Diet-induced uremic condition in rats led to aortic calcification and increased total cholesterol and Pcsk9 levels in plasma, livers, and kidneys. Both human and rat SMCs overexpressing human PCSK9 (SMCs PCSK9 ), cultured in a pro-calcific environment (2.0 mM or 2.4 mM inorganic phosphate, Pi ) showed a significantly higher extracellular calcium (Ca 2+ ) deposition compared to control SMCs. The addition of recombinant human PCSK9 did not increase the extracellular calcification of SMCs, suggesting the involvement of intracellular PCSK9. Accordingly, the further challenge with evolocumab did not affect calcium deposition in hSMCs PCSK9 . Under pro-calcific conditions, SMCs PCSK9 released a higher number of extracellular vesicles (EVs) positive for three tetraspanin molecules, such as CD63, CD9, and CD81. EVs derived from SMCs PCSK9 tended to be more enriched in calcium and alkaline phosphatase (ALP), compared to EVs from control SMCs. In addition, PCSK9 has been detected in SMCs PCSK9 -derived EVs. Finally, SMCs PCSK9 showed an increase in pro-calcific markers, namely bone morphogenetic protein 2 and ALP, and a decrease in anti-calcific mediator matrix GLA protein and osteopontin. Conclusions: Our study reveals a direct role of PCSK9 on vascular calcification induced by higher inorganic phosphate levels associated with renal impairment. This effect appears to be mediated by a switch towards a pro-calcific phenotype of SMCs associated with the release of EVs containing Ca 2+ and ALP. Graphical abstract: Image 1 Highlights: PCSK9 plasma levels are negatively associated with glomerular filtration rate, and atherosclerotic cardiovascular disease further increased PCSK9 plasma levels in a cohort of 594 subjects. PCSK9 plasma levels are increased under uremic conditions in rats, where extensive vascular calcification is observed. Overexpression of PCSK9 in human smooth muscle cells increased extracellular calcium deposition in response to high phosphate concentrations. PCSK9 mediated a switch towards a pro-calcific phenotype of smooth muscle cells associated with the release of extracellular vesicles containing calcium and alkaline phosphatase.